Dental Nonmetric Traits in a Pre-Conquest Sample from Chubut Region of Patagonia, Argentina - Gabriel A. Bollini; Carlos David Rodríguez-Flórez; Sonia E. Colantonio (Dental Anthropology Association, 2008)
Dental morphological trait expressions have been used in anthropology and forensic sciences for determination of biological and geographical affiliations. The present study was carried out with a Chubut preconquest sample from Patagonia, Argentina. 18 skulls with partial dentitions from Chubut (Patagonia) were analyzed. The ASU Dental Anthropology System was used to register the expression grade of all dental traits. In spite of small sample sizes, we can conclude that shovel shape (UI1, UI2), two lingual premolar cusps (UP1, UP2), and hypocone (UM1, UM2) frequencies suggest a Mongoloid (Sinodont) origin.